Digital Twins Empower Higher Education - Lei, JING; Song, Jia-Qing; Wang, Ji-Yan (MASI Mandiri Edukasi, 2024)
This paper explores the application of digital twin technology in higher education and its enabling effect. Through literature review and case studies, this paper studies the generation, basic concepts, technical frameworks, and application scenarios, e.g., in higher education, of digital twins. The results show that digital twin technology can significantly improve the teaching quality and learning effect and optimize educational resource allocation and management efficiency. This paper also discusses the challenges of digital twin technology and the prospects for future development in higher education. It provides new ideas and practical paths for the digital transformation of higher education.